Kecurangan Dalam Laporan Keuangan “Menguji Teori Fraud Triangle” - Langgeng Prayitno Utomo (ITB AAS INDONESIA, 2018)
This study aims to examine the factors that affect the fraudulent financial statements of the company. Fraud detection of financial statements using fraud triangle theory. Based on the theory of fraud triangle there are three factors: pressure, opportunity, and rationalization are used as parameters to detect fraud. The sample of this study used 44 companies in 3 years of observation, where the company is divided into companies that are indications of fraud and not by doing the analysis using the calculation of the underlying M-score, this study used logistic regression, the result that the indication of fraud in this study only can be obtained from external pressure factors on pressure variables and the effectiveness of monitoring on the opportunity variables, this study fails to establish influence in three factors at once ie pressure, opportunity, and rational